Preface to the Special Section: Dense Water Formations in the Northwestern Mediterranean: From the Physical Forcings to the Biogeochemical Consequences. Issue 10 (21st October 2018) - Conan, Pascal; Testor, Pierre; Estournel, Claude; D'Ortenzio, Fabrizio; Pujo‐Pay, Mireille; Durrieu de Madron, Xavier
Abstract: The northwestern Mediterranean Sea is one of the few sites of open‐sea deep convection and dense water formation. The area is characterized by intense air‐sea exchanges favored by the succession of strong northerly and northwesterly winds during autumn and winter that eventually induce deep convection episodes and the formation of the Western Mediterranean Deep Water . This region exhibits a significant spring phytoplankton bloom, which appears to be largely influenced in intensity and diversity by the winter mixing. To understand and resolve the interplay between the atmosphere and ocean, and the impact of ocean circulation and mixing on biogeochemistry, we carried out an unprecedented observational effort during a large experiment between July 2012 and July 2013. A multiplatform approach—combining aircraft, balloons, ships, moorings, floats, and gliders ‐ aimed both at characterizing the dynamics of the atmosphere and at quantifying the physical, biogeochemical, and biological properties of the water masses. Beyond a better understanding of the wind dynamics, the interannual variability of the deep convection, and the seasonal variability of the nutrient distribution and plankton structure in the pelagic ecosystem, the experiment provided a reference data set that was used as a benchmark for advancing the modeling of the surface fluxes, convective processes, dense water formation rates, and physical‐biogeochemical coupling processes. It also represented an opportunity for complementary investigations such as evaluating model parameterizations or studying the role of submesoscale eddies in dense water spreading and biogeochemistry. Key Points: The results of the Dewex operation quantify and accurately describe the dynamics of dense water formations and their effects at subscale and mesoscale Advances concern physics but also biogeochemical budgets, planktonic biodiversity, and trophic levels functioning The special issue also deals with the potential evolution of mechanisms and their impacts on biogeochemistry in the context of global change